Novel approaches of nanoceria with magnetic, photoluminescent, and gas-sensing properties - Rocha, Leandro Silva Rosa [UNESP]; Amoresi, Rafael Aparecido Ciola [UNESP]; Moreno, Henrique Piccoli [UNESP]; Ramirez Gil, Miguel Angel [UNESP]; Ponce, Miguel Adolfo; Foschini, Cesar Renato [UNESP]; Longo, Elson [UNESP]; Simões, Alexandre Zirpoli [UNESP] (ACS Publications, 2020)
The modification of CeO2 with rare-earth elements opens up a wide range of applications as biomedical devices using infrared emission as well as magnetic and gas-sensing devices, once the structural, morphological, photoluminescent, magnetic, electric, and gassensing properties of these systems are strongly correlated to quantum electronic transitions between rare-earth f-states among defective species. Quantitative phase analysis revealed that the nanopowders are free from secondary phases and crystallize in the fluorite-type cubic structure. Magnetic coercive field measurements on the powders indicate that the substitution of cerium with lanthanum (8 wt %), in a fluorite-type cubic structure, created oxygen vacancies and led to a decrease in the fraction of Ce species in the 3+ state, resulting in a stronger roomtemperature ferromagnetic response along with high coercivity (160 Oe). In addition to the magnetic and photoluminescent behavior, a fast response time (5.5 s) was observed after CO exposure, indicating that the defective structure of ceria-based materials corresponds to the key of success in terms of applications using photoluminescent, magnetic, or electrical behaviors.
Novel Approaches of Nanoceria with Magnetic, Photoluminescent, and Gas-Sensing Properties
Keywords: Nanopartículas; Nanoceria; Photoluminescent; Luminescência; Gas-Sensing Properties